Fund conditionality : evolution of principles and practices - Guitián, Manuel; International Monetary Fund. (Washington, D.C. : International Monetary Fund ; Request from External Relations Dept., Attention--Publications, International Monetary Fund, 1981)
The paper examines the principle and practices of conditionality as they have evolved and as they are applied.
"Evolved from a series of three articles published in Finance and development in its December 1980, March 1981, and June 1981 issues."
Includes bibliographical references: p. 47-50.
oo 16/04/2019
Loans
Keywords: Balance of payments; Conditionality (International relations)